The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/13548506.2017.1344256
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and occupational stress in the medical residents of Oncology, Haematology and Radiotherapy: a prevalence and predictors study in Portugal

Abstract: Burnout is a professional syndrome associated with stress caused by overwork. Our aim was to calculate the prevalence of burnout and stress on medical residents of Oncology, Haematology and Radiotherapy in Portugal, as well as to determine predictors of burnout and stress. An anonymous questionnaire was applied (n = 118). Statistical analysis consisted of a descriptive and inferential analysis. The prevalence of burnout and stress was calculated to be 45.2 and 50%, respectively. The dimensions that generated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
2
10
1
2
Order By: Relevance
“…Although JSM-Gevaluates a number of different aspects, most of the items of the questionnaire are related to workload, which is considered to be the most important stressor leading to higher burnout levels amongst residents. Studies from different countries like Japan, [26] Portugal, [27] Greece [24, 25] and Malaysia [28] revealed similar findings, indicating overwork as the most important predictor for residents burnout. Moreover, a number of studies have shown that the amount of responsibilities and stressors related to career development, that JSM-G also evaluates, are strongly related to residents’ exhaustion [24, 28].…”
Section: Discussionmentioning
confidence: 73%
“…Although JSM-Gevaluates a number of different aspects, most of the items of the questionnaire are related to workload, which is considered to be the most important stressor leading to higher burnout levels amongst residents. Studies from different countries like Japan, [26] Portugal, [27] Greece [24, 25] and Malaysia [28] revealed similar findings, indicating overwork as the most important predictor for residents burnout. Moreover, a number of studies have shown that the amount of responsibilities and stressors related to career development, that JSM-G also evaluates, are strongly related to residents’ exhaustion [24, 28].…”
Section: Discussionmentioning
confidence: 73%
“…The strongest relationship was between burnout and stress, a relationship well-described in the literature with regard to health care workers in general. 36 , 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…The strongest relationship was between burnout and stress, a relationship well-described in the literature with regard to health care workers in general. 36,47,48 Understanding the factors that predict burnout may offer us important targets in prevention. While perceived stress was the most strongly correlated factor related to burnout in crosssectional analysis, it was not significantly predictive of confidence in providing compassionate care or burnout in regression analysis over our 3-month study period after controlling for their baseline scores.…”
Section: Discussionmentioning
confidence: 99%
“…The “professional supervision,” seen as necessary by some social workers, as a moment of reflection and professional and emotional support, is perceived as a “challenge” as it is not present in all services. However, the supervision tool would allow to address some of the critical issues (Matyushkina, 2019; Rae et al, 2017) highlighted by social workers such as “overwork,” “lack of competence,” and a “sense of abandonment,” which in the literature are considered factors that can lead to work burnout (George-Levi et al, 2020; Joaquim et al, 2018). Indeed, according to Robinson (2013), the professional supervision function, due to the ethically demanding nature of the work and the impact on the health of social workers, improves support for those who work in particular with asylum seekers and refugees.…”
Section: Discussionmentioning
confidence: 99%